Philippe Ariès and his files: from the memory of the historian to that of the militant (Tempo e Argumento, 2013)
This article aims to discuss the trajectory of the historian Philippe Ariès by means of the analysis of "Philippe Aries files", which were gathered in the late 1990s. It is divided in three parts: the first part makes brief exposition of the major stages of the journey of Philippe Ariès between political culture and the vocation of the historian; the second explains how his files were constituted, privileging the figure of the historian withoutmasking the militant, since the two identities are strong. Finally, we analyze the conditions for their update and the tensions raised by the return of the figure of the militant over that of the historian mainly considering the reception of his posthumous works from 1986.
Keywords: particular archives; history of childhood; political culture; militancy